FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN KEMATIAN PADA PASIEN MENINGITIS DI RSUP DR. MOH. HUSEIN PALEMBANG - Dewie Susan; Irfanuddin Irfanuddin; Andika Okparasta (NEURONA, 2021)
Introduction: Meningitis is a universal health problem and a medical emergency, with high morbidity and mortality. The meningitis mortality rate is still relatively high even though more sensitive antibiotics have been given, better intensive care, advances in neurosurgery techniques, and advances in neuro-diagnostic and laboratory technology. Aims: To identify the risk factors that infuence the incidence of death in meningitis patients and to analyze the survival rate of meningitis patients admitted to dr. Moh. Husein Palembang Hospital. Methods: This study was an analytical observational study using a prospective cohort method from April to November 2020. Sampling was carried out by consecutive sampling. This study will observe mortality at the end of hospitalization and 90 days after hospitalization. Results: Of 19 study subjects, 12 subjects were alive, and seven died until the end of the observation. In bivariate analysis, infuencing factors were GCS score ≤ 11, cranial nerve paresis, cerebrospinal fuid culture, and abnormal head CT scan. In multivariate analysis, the most infuential factor was the GCS score ≤ 11 (p = 0.003). Mmeanwhile, the mean incidence mortality of bacterial meningitis occurred on day 6.5 ± 7.68, for tuberculous meningitis on day 22.5 ± 24.74, for fungal meningitis on day 68, while viral meningitis did not show any mortality.Discussion: Decreased consciousness is the leading risk factor that infuences the incidence of death in meningitis patients. Keywords: meningitis, mortality, survival analysis.